Suppression of liquation cracking susceptibility via pre-weld heat treatment for manufacturing of CM247LC superalloy turbine blade welds - Eun-Joon Chun; Ye-Seon Jeong; Kyeong-Min Kim; Hyungsoo Lee; Seong-Moon Seo (Journal of Advanced Joining Processes, 2021)
In this study, the weldability of as-cast CM247LC superalloy was metallurgically evaluated for turbine blade applications in terms of its hot cracking behavior and susceptibility. For this purpose, a real blade was manufactured using a directional solidification casting process, and gas tungsten arc welding was performed at the tip and cavity of the upper blade. Hot cracking was confirmed in the heat-affected zone of the gas tungsten arc welds, and the cracks were characterized as liquation cracks. Metallurgical solutions to suppress the liquation cracking susceptibility were derived via visualization-based spot-Varestraint test. The alloy subjected to aging treatment exhibited the lowest liquation cracking susceptibility (liquation cracking temperature range: 66 K), while the as-cast alloy specimen exhibited the highest (liquation cracking temperature range: 620 K). The metallurgical mechanisms of the liquation cracking susceptibility of as-cast CM247LC welds were elucidated via microstructural analyses and thermodynamic calculations. The suppressed liquation cracking susceptibility of the aged CM247LC could be explained as follows: (i) reduced MC-type carbide, which lowered the local solidus temperature compared with the equilibrium solidus temperature of CM247LC and (ii) increased solidus temperature owing to γ’ precipitation γ’ within the γ matrix. To validate the suppressed liquation cracking susceptibility of the aged CM247LC specimen in real welding, it was subjected to gas tungsten arc welding. The results indicated considerable suppression of liquation cracking compared with as-cast welds; in particular, the reduced liquation cracking temperature range was well-reflected in the welding.